Crohn's disease is facilitated by a disturbance of programmed death‐1 ligand 2 on blood dendritic cells. Issue 7 (25th July 2019) - Faleiro, Rebecca; Liu, Ji; Karunarathne, Deshapriya; Edmundson, Aleksandra; Winterford, Clay; Nguyen, Tam Hong; Simms, Lisa A; Radford‐Smith, Graham; Wykes, Michelle
Abstract: Objective: Crohn's disease (CD) is characterised by inflammation, predominantly associated with ilea. To investigate the basis for this inflammation in patients with CD, we examined dendritic cells (DC) which are pivotal for maintenance of immunological tolerance in the gut. Methods: Ileal biopsies and blood DCs from CD patients and controls were examined by microscopy and flow cytometry for PD‐L1 and PD‐L2 expression, as PD‐L1 has been implicated in colitis but the contribution of PD‐L2 is less clear. In vitro studies, of blood samples from CD patients, were used to demonstrate a functional role for PD‐L2 in disease pathogenesis. Results: Quantitative microscopy of CD11c + DCs in inflamed and noninflamed ilea from CD patient showed > 75% loss of these cells from the villi, lamina propria and Peyer's patches compared with non‐CD controls. Given this loss of DCs from ilia of CD patients, we hypothesised DCs may have migrated to the blood as these patients can have extra‐intestinal symptoms. We thus examined blood DCs from CD patients by flow cytometry and found significant increases in PD‐L1 and PD‐L2 expression compared with control samples. Microscopy revealed an aggregated form of PD‐L2 expression, known to drive Th1 immunity, in CD patients but not in controls. In vitro functional studies with PD‐L2 blockade confirmed PD‐L2 contributes significantly to the secretion of pro‐inflammatory cytokines known to cause disease pathogenesis. Conclusion: Taken together, this study shows that PD‐L2 can influence the progression of CD and blockade of PD‐L2 may have therapeutic potential. Abstract : The pathology of Crohn's disease is supported by excessive production of TNF‐α and INF‐γ production. This study shows that dendritic cells (DC) migrate away from the ileum of patients with Crohn's disease and that DCs in the blood of these patients overexpress PD‐L2 which can overdrive TNF‐α and INF‐γ production.